Hemoglobin uptake and utilization by human protozoan parasites: a review - Reyes-López, Magda; Aguirre-Armenta, Beatriz; Piña-Vázquez, Carolina; de la Garza, Mireya; Serrano-Luna, Jesús (Frontiers in Cellular and Infection Microbiology, 2023)
The protozoan disease is a major global health concern. Amoebiasis, leishmaniasis, Chagas disease, and African sleeping sickness affect several million people worldwide, leading to millions of deaths annually and immense social and economic problems. Iron is an essential nutrient for nearly all microbes, including invading pathogens. The majority of iron in mammalian hosts is stored intracellularly in proteins, such as ferritin and hemoglobin (Hb). Hb, present in blood erythrocytes, is a very important source of iron and amino acids for pathogenic microorganisms ranging from bacteria to eukaryotic pathogens, such as worms, protozoa, yeast, and fungi. These organisms have developed adequate mechanisms to obtain Hb or its byproducts (heme and globin) from the host. One of the major virulence factors identified in parasites is parasite-derived proteases, essential for host tissue degradation, immune evasion, and nutrient acquisition. The production of Hb-degrading proteases is a Hb uptake mechanism that degrades globin in amino acids and facilitates heme release. This review aims to provide an overview of the Hb and heme-uptake mechanisms utilized by human pathogenic protozoa to survive inside the host.